Hot Melt Adhesives
The hot melt adhesive formulation with elastomer, mineral oil, and tackifier addresses short solidification and thermal cycle issues, providing strong and durable bonding to polypropylene surfaces, even at varying temperatures.
Patent Information
- Application Number
- JP2021006722
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-19
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-01-19
AI Technical Summary
Existing hot melt adhesives face challenges with short solidification times, poor adhesion to polypropylene, and low thermal cycle durability, especially when bonding areas with large adhesive surfaces, leading to premature hardening and peeling due to temperature changes.
A hot melt adhesive formulation containing an elastomer, mineral oil, and a tackifier, preferably a styrene-isoprene-styrene block copolymer, with specific adhesive strength and heat breakdown temperature ranges, allowing for extended bonding time and improved durability.
The adhesive achieves excellent adhesion to polypropylene, maintains strength across temperature cycles, and allows for easy application and bonding, even after prolonged exposure to 25°C, with a heat breakdown temperature of 70°C or higher, ensuring durability and ease of handling.
Smart Images

Figure 0007608842000002 
Figure 0007608842000003 
Figure 0007608842000004
Abstract
Description
[Technical field]
[0001] The present invention relates to hot melt adhesives. [Background technology]
[0002] 2. Description of the Related Art Resin laminates bonded and laminated with hot melt adhesives have been widely used as building materials, electromagnetic wave absorbing materials, building panels, automotive interior materials, containers, heat insulating materials, masking tapes, hoses, and special coating materials. An example of a conventional hot melt adhesive is described in Patent Document 1.
[0003] Patent Document 1 describes a hot melt adhesive comprising, as essential components, an amorphous poly(α-olefin) (A) having a melt viscosity in the range of 500 to 100,000 mPa·s / 190°C, a tackifier resin (B) having a softening point of 110°C or higher as measured by the ring and ball method, and a polypropylene wax (C) having a melting point of 120°C or higher, in which the weight ratio of (A) to (C) is 100 / 50 to 100 / 100. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-284575 A
[0005] Such hot melt adhesives are strongly required to have excellent adhesion to adherends such as polypropylene and excellent durability against thermal cycles due to the harsh environments in which they are used, not limited to automotive and building material applications. On the other hand, hot melt adhesives have the characteristic that after applying the molten adhesive to one adherend, it takes a short time to solidify before the other adherend is attached and fixed, but if the solidification time is extremely short, the adhesive in the first applied area will solidify before the adhesive is completely applied to the entire area with a large adhesive surface area, and adhesion will not be possible. In such cases, there are pressure-sensitive adhesives that can increase the wettability of the adherend and bond it to the other adherend simply by applying pressure at 25°C, but these adhesives generally have low heat resistance, and when adherends with different linear expansion coefficients are bonded together, the adhesive layer cannot absorb the stress caused by expansion and contraction due to temperature changes, and they peel off, which is called low durability against heat and cold cycles. Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a hot melt adhesive which has excellent adhesive strength, particularly to polypropylene-based adherends, and durability to thermal cycles, and which is capable of bonding even in areas with a large bonding area. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> A 120μm thick film of hot melt adhesive was applied to a 25mm x 25mm area of polypropylene plate A, and then another polypropylene plate B was placed on top of it, and the adhesive was applied with a pressure of 2kgf / cm 2 The test piece obtained by pressing for 10 seconds at a pressure of 0.15 MPa or more is left to stand at 25°C for 16 hours, and then, in accordance with JIS K6850, the polypropylene plate A and the polypropylene plate B are pulled in opposite directions at a speed of 50 mm / min at 25°C in the surface direction of the two polypropylene plates. A 200g weight is attached to one end of the test piece, and the piece is left to stand at 38°C for 15 minutes. The temperature is then raised at a rate of 0.4°C / min. When the adhesive part can no longer withstand the load of the weight and the weight falls, the temperature is 70°C or higher. Hot melt adhesive. <2> Contains elastomer, mineral oil, and tackifier <1> The hot melt adhesive according to claim 1. <3> The elastomer comprises a styrene copolymer. <2> The hot melt adhesive according to claim 1. <4> The elastomer comprises a block copolymer. <2> or <3> The hot melt adhesive according to claim 1. <5> The elastomer comprises a styrene-isoprene-styrene block copolymer. <2> ~ <4> 13. The hot melt adhesive according to claim 12, <6> Further containing an antioxidant <2> ~ <5> 13. The hot melt adhesive according to claim 12, <7> This is a hot melt adhesive for producing a resin laminate consisting of an elastically deformable resin layer and a flexible surface layer. <1> ~ <6> 13. The hot melt adhesive according to claim 12, Effect of the Invention
[0008] According to one embodiment of the present invention, it is possible to provide a hot melt adhesive that has excellent adhesive strength and durability against thermal cycles, and is capable of bonding even in areas with a large bonding area. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view of an example of a resin laminate according to the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing an adhesive strength measurement test of a test piece obtained using a hot melt adhesive according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a heat destruction temperature measurement test of a test piece obtained using the hot melt adhesive according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The following description of the constituent elements may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, the word "to" is used to mean that the numerical values before and after it are included as the lower limit and upper limit. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the term "step" in this specification includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In the present invention, "mass%" and "weight%" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Also, in the present invention, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. The present invention will be described in detail below.
[0011] (Hot melt adhesive) The hot melt adhesive of the present invention has excellent adhesion to polypropylene in particular. A 120 μm thick film of hot melt adhesive is applied to a 25 mm × 25 mm area of polypropylene plate A, and then another polypropylene plate B is placed on top of it. The adhesive is then compressed under a pressure of 2 kgf / cm. 2A test piece was obtained by pressing at a pressure of 100 g for 10 seconds, and then allowed to stand at 25°C for 16 hours. After that, in accordance with JIS K6850, polypropylene plate A and polypropylene plate B were pulled in opposite directions in the plane direction of the two polypropylene plates at a rate of 50 mm / min at 25°C, and the adhesive strength was 0.15 MPa or more. A 200 g weight was attached to one end of the test piece, and the test piece was allowed to stand at 38°C for 15 minutes. The temperature was then raised at a rate of 0.4°C / min, and the temperature at which the adhesive portion could no longer withstand the load of the weight and the weight fell (hereinafter also referred to as the "heat destruction temperature") was 70°C or more. Furthermore, the hot melt adhesive according to the present invention can be suitably used as a hot melt adhesive for producing a resin laminate comprising an elastically deformable resin layer and a flexible surface layer.
[0012] As a result of extensive investigations, the present inventors have found that by adopting the above-mentioned configuration, it is possible to provide a hot melt adhesive having excellent durability against thermal cycles. When the adhesive strength and the heat destruction temperature satisfy the above ranges, the adhesive strength is excellent, and the adhesive strength retention is excellent at low temperatures (e.g., 25°C or lower) and at high temperatures (e.g., 70°C or higher), and the durability to thermal cycles is excellent. In the present invention, the "cold-heat cycle" in "cold-heat cycle durability" refers to a cycle of maintaining a high temperature (e.g., 60°C for 2 hours) followed by maintaining a low temperature (e.g., -20°C for 2 hours), unless otherwise specified, and the "cold-heat cycle durability" refers to the durability when this cycle is repeated.
[0013] Furthermore, when a resin laminate is produced using the hot melt adhesive of the present invention, not only does it have excellent thermal cycle durability, but it also has an appropriate solidification time, making it easy to apply, adhere, and perform other operations of the hot melt adhesive, resulting in excellent productivity.
[0014] Each of the constituent elements according to the present invention will be described in detail below.
[0015] <Adhesive strength> The hot melt adhesive of the present disclosure has an adhesive strength of 0.15 MPa or more when a 120 μm-thick film-like hot melt adhesive is applied to a 25 mm × 25 mm area on polypropylene plate A, another polypropylene plate B is then placed on top of it, and the polypropylene plate A and the polypropylene plate B are pulled in opposite directions in the surface direction of the two polypropylene plates at a speed of 50 mm / min at 25°C in accordance with JIS K6850. From the viewpoints of adhesiveness and durability against thermal cycles, the adhesive strength is preferably 0.18 MPa or more, and particularly preferably 0.25 MPa or more and 1.0 MPa or less.
[0016] Specifically, the adhesive strength can be measured by the following method. The hot melt adhesive was sandwiched between two Teflon (registered trademark) sheets and formed into a film-like hot melt adhesive with a thickness of 120 μm using a heating press adjusted to 140°C. This film-like hot melt adhesive was then transferred from one end of a polypropylene plate A, which was 25 mm wide, 50 mm long and 2 mm thick, to an area of 25 mm x 25 mm. After that, another polypropylene plate B of the same shape was placed on top of the area of polypropylene plate A where the film-like hot melt adhesive had been transferred, so that the area where the film-like hot melt adhesive had not been transferred did not overlap, and the plate was subjected to a pressure of 2 kgf / cm 2 The test piece obtained by pressing for 10 seconds at a pressure of 1000 g / cm is left at rest at 25°C for 16 hours, and then, in accordance with JIS K6850 (1999), the polypropylene plate A and the polypropylene plate B are pulled in opposite directions at a speed of 50 mm / min at 25°C in the surface direction of the two polypropylene plates, and the magnitude of the force (shear adhesive strength) at which shear failure occurs is defined as the adhesive strength (MPa). Figure 2 is a schematic diagram of the test piece and weight in the adhesive strength measurement test. Figure 2 shows the side of the test piece, and the film-like hot melt adhesive according to the present invention is provided in a range of 25 mm from the end in the length direction, and the polypropylene plate PA (the polypropylene plate A) and the polypropylene plate PB (the polypropylene plate B) are bonded. The arrow in Figure 2 indicates the tensile direction.
[0017] <Heat destruction temperature> The hot melt adhesive of the present invention has a temperature (heat destruction temperature) of 70°C or higher when a 200g weight is attached to one end of the test piece, which is left to stand at 38°C for 15 minutes and then heated at a rate of 0.4°C / min., at which the bonded area can no longer withstand the load of the weight and the weight falls. From the viewpoints of durability against thermal cycles and ease of adhesion, the heat destruction temperature is preferably 75° C. or higher, more preferably 80° C. or higher, and particularly preferably 82° C. or higher and 140° C. or lower.
[0018] Specifically, the heat destruction temperature can be measured by the following method. A test piece obtained in the same manner as in the measurement of adhesive strength was used, a 200g weight was attached to one end of the test piece, and the other end of the test piece was fixed so that the part where the weight was attached was the lower part in the weight direction and the test piece was perpendicular to the horizontal plane. The test piece was left to stand at 38°C for 15 minutes, and then the temperature was increased at a rate of 0.4°C / min. The temperature was measured when the adhesive part of the test piece could no longer withstand the load of the weight and the weight fell. Figure 3 is a schematic diagram of the test piece and the weight in the heat destruction temperature measurement test. Figure 3 shows the side of the test piece as in Figure 2, and a weight W is attached to the lower polypropylene plate PB.
[0019] <Adhesive time> The hot melt adhesive according to the present disclosure can increase the wettability of an adherend simply by applying pressure at 25°C, and has a long adhesive life that allows it to bond to another adherend. Specifically, it is preferable that the adhesive can be bonded even after being left for 10 minutes in an environment of 25° C., more preferably 20 minutes or more, and even more preferably 30 minutes or more. If the adhesive can be bonded even after being left for this time, even if a phenomenon occurs in which the equipment or production is temporarily stopped due to some kind of trouble in the production line for bonding, production can be resumed after recovery without wasting the adherend to which the adhesive is applied.
[0020] Specifically, the adhesion time can be measured by the following method. A 120μm thick film of hot melt adhesive is applied to a 25mm x 25mm area on polypropylene plate A, and after leaving it in a 25℃ environment for a specified time, another polypropylene plate B is placed on top of it, and the adhesive is subjected to a pressure of 2kgf / cm 2 The test piece obtained by pressing for 10 seconds at a pressure of 100 mm was left to stand at 25°C for 16 hours, and then the polypropylene plate A and the polypropylene plate B were pulled in opposite directions in the surface direction of the two polypropylene plates at a speed of 50 mm / min at 25°C in accordance with JIS K6850. The time at which the adhesive strength was 0.15 MPa or more was defined as the adhesive time. The time from when the adhesive was applied to an area of 25 mm x 25 mm on polypropylene plate A until another polypropylene plate B was placed on top of it was evaluated every 10 minutes up to a maximum of 30 minutes.
[0021] <Composition> The hot melt adhesive according to the present invention is not particularly limited in composition so long as the adhesive strength and the heat destruction temperature satisfy the above-mentioned ranges; however, from the viewpoints of thermal cycle durability, adhesiveness and handleability, it preferably contains an elastomer, more preferably contains an elastomer, a mineral oil and a tackifier (also referred to as a "tackifier"), and even more preferably contains an elastomer, a mineral oil, a tackifier and an antioxidant.
[0022] -Elastomer- From the viewpoints of durability against thermal cycles, adhesiveness, and handleability, the hot melt adhesive according to the present invention preferably contains an elastomer. In the present invention, the "elastomer" refers to a polymer having rubber elasticity at room temperature. The elastomer is not particularly limited, and known materials can be used, such as styrene-butadiene rubber (SBR), polyolefin, polyester resin, and styrene block copolymer. Among these, from the viewpoints of durability against thermal cycles and adhesiveness, the elastomer preferably contains a styrene copolymer, more preferably contains a styrene block copolymer, and particularly preferably contains a styrene-isoprene-styrene block copolymer. From the viewpoints of durability against thermal cycles and adhesiveness, the elastomer is preferably a block copolymer. The hot melt adhesive of the present invention may contain one type of elastomer alone or two or more types, but from the viewpoint of thermal cycle durability and adhesiveness, it is preferable that the adhesive contains two or more types of elastomers, and more preferable that the adhesive contains two or more types of styrene-isoprene-styrene block copolymers. The hot melt adhesive of the present invention preferably contains two to four types of the elastomers.
[0023] Examples of the styrene block copolymer include styrene-isoprene-styrene block copolymer (SIS), styrene-butadiene-styrene block copolymer (SBS), styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene-isoprene / propylene-styrene block copolymer (SIBS), styrene-butylene / butene-styrene block copolymer (SBBS), etc. Among them, styrene-isoprene-styrene block copolymer (SIS) is preferred. The styrene-isoprene-styrene block copolymer used in the present invention may be of either a linear type or a radial type. In particular, from the viewpoints of thermal cycle durability and adhesiveness, it is particularly preferable that the hot melt adhesive according to the present invention contains, as the elastomer, both a linear styrene-isoprene-styrene block copolymer and a radial styrene-isoprene-styrene block copolymer.
[0024] From the viewpoints of thermal cycle durability and adhesiveness, the MFR (melt mass flow rate) of the elastomer is preferably 0.5 g / 10 min to 100 g / 10 min, more preferably 1 g / 10 min to 50 g / 10 min, further preferably 2 g / 10 min to 30 g / 10 min, and particularly preferably 5 g / 10 min to 20 g / 10 min. The MFR of the elastomer in the present invention is measured in accordance with JIS K7210 (2014) under conditions of a test temperature of 200°C and a test load of 5 kg.
[0025] From the viewpoints of thermal cycle durability, adhesiveness and handleability, the content of the elastomer is preferably 10% by mass or more and 80% by mass or less, more preferably 20% by mass or more and 65% by mass or less, and particularly preferably 30% by mass or more and 50% by mass or less, based on the total mass of the hot melt adhesive. When the content of the elastomer is 30% by mass or more, the cohesive strength of the adhesive is sufficient and the heat destruction temperature is high, whereas when the content is 50% by mass or less, the melt viscosity during heating and application of the adhesive does not become high, improving application workability.
[0026] -Mineral oil- The hot melt adhesive according to the present invention preferably contains a mineral oil from the viewpoints of durability against thermal cycles, adhesion at room temperature (for example, 25° C.), and ease of handling. The tackiness at room temperature is related to the improvement of the adhesiveness by increasing the wettability to the adherend. The mineral oil in the present invention refers to a hydrocarbon compound, and is preferably a hydrocarbon compound derived from underground resources such as petroleum, natural gas, and coal. Moreover, the mineral oil is preferably a liquid compound at 25°C. Furthermore, from the viewpoints of durability against thermal cycles, adhesion at 25° C., and ease of handling, it is preferable that the mineral oil is a compound that is compatible with the elastomer and a tackifier described below.
[0027] Preferred examples of the mineral oil include aromatic (aromatic) hydrocarbon compounds, naphthenic (cyclocyclic) hydrocarbon compounds, paraffinic (aliphatic) hydrocarbon compounds, and mixtures thereof. Among these, from the viewpoints of thermal cycle durability, adhesion at 25°C, and handleability, it is preferable that the mineral oil contains a paraffin-based hydrocarbon compound, it is more preferable that the mineral oil contains a paraffin-based hydrocarbon compound in the largest amount of the three types of hydrocarbon compounds relative to the total mass of the mineral oil, and it is particularly preferable that the hot melt adhesive contains a paraffin-based hydrocarbon compound in an amount of 50 mass% or more relative to the total mass of the mineral oil contained in the hot melt adhesive. Furthermore, from the viewpoints of thermal cycle durability, adhesion at 25°C and handleability, the mineral oil preferably contains aromatic hydrocarbon compounds in an amount of 20 mass% or less, relative to the total mass of the mineral oil contained in the hot melt adhesive, more preferably contains aromatic hydrocarbon compounds in an amount of 10 mass% or less, relative to the total mass of the mineral oil contained in the hot melt adhesive, even more preferably contains aromatic hydrocarbon compounds in an amount of 1 mass% or less, relative to the total mass of the mineral oil contained in the hot melt adhesive, and particularly preferably contains no aromatic hydrocarbon compounds.
[0028] As the mineral oil, commercially available products can also be used. For example, Process Oil PW90 (manufactured by Idemitsu Kosan Co., Ltd.), Sunpure NX46, Sunpure NX90, Sunpure N90-A (all manufactured by Nippon Sun Oil Co., Ltd.) and the like can be mentioned.
[0029] The mineral oils may be used alone or in combination of two or more. From the viewpoints of thermal cycle durability, adhesion at 25°C, and handleability, the content of the mineral oil is preferably from 1 mass% to 30 mass% relative to the total mass of the hot melt adhesive, more preferably from 5 mass% to 25 mass%, and particularly preferably from 10 mass% to 20 mass%. From the viewpoints of thermal cycle durability, adhesion at 25°C, and handleability, the mass ratio of the mineral oil content to the elastomer content in the hot melt adhesive according to the present invention is preferably 0.05 or more and 1.2 or less, more preferably 0.1 or more and 1.0 or less, even more preferably 0.2 or more and 0.8 or less, and particularly preferably 0.3 or more and 0.5 or less, i.e., mineral oil content / elastomer content.
[0030] -Tacky Fire- From the viewpoints of durability against thermal cycles, adhesiveness at 25° C., and handleability, the hot melt adhesive according to the present invention preferably contains a tackifier (tackifier). Examples of the tackifier include petroleum resins; rosin derivatives such as rosin ester, gum rosin, tall oil rosin, hydrogenated rosin ester, maleated rosin, and disproportionated rosin ester; terpene-based resins mainly composed of terpene phenol resins, α-pinene, β-pinene, limonene, and the like; coumarone-indene-based resins; hydrogenated aromatic copolymers; styrene-based resins; phenol-based resins; xylene-based resins; and (meth)acrylic polymers.
[0031] In particular, from the viewpoints of thermal cycle durability, adhesion, tackiness at 25°C and handleability, the hot melt adhesive according to the present invention preferably contains, as the tackifier, at least one compound selected from the group consisting of petroleum resins, rosin derivatives, and terpene resins, more preferably at least one compound selected from the group consisting of C5 petroleum resins, rosin esters, and terpene phenolic resins, even more preferably C5 petroleum resins, particularly preferably C5 petroleum resins and rosin esters, and most preferably C5 petroleum resins, rosin esters, and terpene phenolic resins.
[0032] C5 petroleum resin is a hydrocarbon resin obtained by polymerizing a C5 fraction produced by cracking naphtha. The C5 fraction includes, for example, isoprene, cyclopentene, piperylene, and polymerized products thereof. In addition, since C5 petroleum resin has monomer units derived from isoprene, when SIS is used as the elastomer, it has excellent compatibility with the isoprene-derived monomer units of SIS. Therefore, from the viewpoints of thermal cycle durability and adhesion at 25°C, it is particularly preferable that the hot melt adhesive according to the present invention contains C5 petroleum resin and SIS. Rosin ester is a derivative in which at least a portion of the carboxy groups in rosin are esterified. The terpene phenol resin is a resin in which a terpene resin is copolymerized with phenol. In addition, since the terpene phenol resin has a phenol structure, when SIS is used as the elastomer, it has excellent compatibility with the styrene-derived monomer units of the SIS. Therefore, it is particularly preferable that the hot melt adhesive of the present invention contains a terpene phenol resin and SIS from the viewpoints of durability against cold and heat cycles and heat destruction temperature.
[0033] The tackifiers may be used alone or in combination of two or more kinds. From the viewpoints of thermal cycle durability, adhesiveness, tackiness at 25°C and handleability, the hot melt adhesive of the present invention preferably contains two or more kinds of tackifiers, more preferably contains two to four kinds, and particularly preferably contains three kinds. The content of the tackifier is preferably from 1% by mass to 70% by mass, more preferably from 10% by mass to 65% by mass, even more preferably from 20% by mass to 60% by mass, and particularly preferably from 30% by mass to 55% by mass, based on the total mass of the hot melt adhesive, from the viewpoints of durability against thermal cycles, adhesion at 25° C. When the content of the tackifier is 30% by mass or more, sufficient adhesiveness is exhibited, and when it is 55% by mass or less, the adhesive layer does not harden and can sufficiently follow the dimensional change of the adherend during thermal cycles. From the viewpoints of thermal cycle durability, adhesion at 25°C, and handleability, the mass ratio of the tackifier content to the elastomer content in the hot melt adhesive of the present invention is preferably tackifier content / elastomer content = 0.5 or more and 5.0 or less, more preferably 0.8 or more and 4.0 or less, even more preferably 1.0 or more and 2.0 or less, and particularly preferably more than 1.0 and 1.5 or less.
[0034] -Antioxidants- From the viewpoints of thermal cycle durability and storage stability, the hot melt adhesive according to the present invention preferably contains an antioxidant. The antioxidant is not particularly limited, and any known antioxidant can be used. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-containing antioxidants, hydroquinone-based antioxidants, quinoline-based antioxidants, hydrazines, and urea-based antioxidants. Among these, phenol-based antioxidants are preferred, and hindered phenol-based antioxidants are more preferred.
[0035] Examples of the phenol-based antioxidant include 2,6-di-t-butyl-p-cresol (BHT), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), stearyl-β-(3,5-di-t-butyl-4-hydroxyphenol)propionate, tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, 1,2-diphenyl-2,3-diphenyl-2,4-diphenyl-2,5 ... ,3,5-trimethyl-2,4,6-tris(3,5-di-t-4-hydroxybenzyl)benzene, 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenol)butane, pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 1,1-bis(4-oxyphenyl)cyclohexane, dialkylphenol sulfides, alkylphenol condensates, styrenated phenol, etc. Among these, a hindered phenol-based antioxidant having one or two t-butyl groups on the aromatic ring adjacent to the carbon atom to which a phenolic hydroxy group is bonded is preferred, and pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] is more preferred. Examples of the amine-based antioxidant include N,N'-di-2-naphthyl-p-phenylenediamine, phenyl-α-naphthylamine, phenyl-β-naphthylamine, 4,4'-dimethoxydiphenylamine, N,N'-diphenyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, aldol-α-naphthylamine, 4,4'-diaminodiphenylmethane, acetaldehyde aniline, and reaction products of diphenylamine and acetone.
[0036] The antioxidants may be used alone or in combination of two or more. From the viewpoints of thermal cycle durability and storage stability, the content of the antioxidant is preferably from 0.001% by mass to 10% by mass, more preferably from 0.01% by mass to 5% by mass, and particularly preferably from 0.05% by mass to 1% by mass, relative to the total mass of the hot melt adhesive.
[0037] -Other ingredients- The hot melt adhesive according to the present invention may further contain other components. Examples of other components include fillers, processing aids, flame retardants, flow control agents, deodorants, antibacterial agents, adhesion promoters, and pigments.
[0038] Examples of fillers that can be used include fumed silica, surface-treated fumed silica, precipitated silica, diatomaceous earth, quartz powder, calcium carbonate, and carbon black. By including a filler, it is possible to improve the heat resistance, elastic modulus, blocking resistance, and the like. Examples of the processing aid include low viscosity silicone oils, resins, and silane compounds having silanol groups or alkoxysilyl groups at the ends. Examples of the heat resistance improver include iron octoate, iron oxide, Mn-based compounds, Ni-based compounds, Cu-based compounds, Zr-based compounds, Ce-based compounds, W-based compounds, titanium oxide, and fumed titanium oxide. To further enhance the flame retardant effect, iron oxide, titanium oxide, carbon black, phosphorus compounds, nitrogen compounds, etc. may be used.
[0039] The other components may be used alone or in combination of two or more. The content of the other components is not particularly limited, but is preferably 5% by mass or less, and more preferably 1% by mass or less, based on the total mass of the hot melt adhesive.
[0040] <Softening point> The softening point of the hot melt adhesive according to the present invention is preferably less than 180°C, more preferably from 70°C to 160°C, and particularly preferably from 90°C to 140°C, from the viewpoints of heat resistance and processability. The softening point of the hot melt adhesive can be measured in accordance with JIS K6863 (1994).
[0041] (Resin laminate) The hot melt adhesive of the present invention can be used to produce a resin laminate. The resin laminate is a resin laminate having two identical or different resin layers and having a layer of the hot melt adhesive of the present invention between the resin layers. The resin laminate may further have a support layer having a lower elastic modulus or rigidity than the resin layer, and may have a layer of the hot melt adhesive according to the present invention between the resin layer and the support layer to bond the resin layer and the support layer. Hereinafter, in order to distinguish between the two resin layers laminated on the support layer, the resin layer adhered to the support layer will be referred to as the "resin layer," and the resin layer not adhered to the support layer will be referred to as the "surface layer."
[0042] <Adhesive layer> The resin laminate has a layer (also referred to as an "adhesive layer") made of the hot melt adhesive of the present invention, and from the viewpoint of thermal cycle durability, it is preferable to have a layer made of the hot melt adhesive of the present invention between both the surface layer and the resin layer, and between the resin layer and the support layer.
[0043] The thickness of the adhesive layer is not particularly limited, regardless of the position of the adhesive layer as described above, but from the viewpoints of dimensional accuracy, thermal cycle durability, adhesion and handleability of the surface layer, resin layer and support layer, it is preferably 50 μm or more and 500 μm or less, more preferably 100 μm or more and 300 μm or less, and particularly preferably 120 μm or more and 200 μm or less, for each independently.
[0044] <Surface layer> The material for the surface layer is not particularly limited, but examples include PVC (polyvinyl chloride), polypropylene, polyethylene, urethane resin, polyester resin, various elastomers based on styrene, polyester, olefin, and acrylic, EVA, EPDM, silicone rubber, and other hard rubbers, or materials adjusted to a hardness that is sufficient for durability, or composite materials based on these and added with fillers or reinforcing materials.
[0045] The thickness of the surface layer can be appropriately selected depending on the desired shape, water resistance, chemical resistance, abrasion resistance, impact resistance, and the like. The thickness of the surface layer is preferably smaller than that of the resin layer, and the surface layer may be flexible. The surface layer may have any shape depending on the application, and may have recesses and / or protrusions or printing on the surface. The shapes and sizes of the recesses and protrusions are not particularly limited and can be selected arbitrarily as desired. When the resin laminate is used for a building panel or the like, the surface layer may be subjected to a water-repellent treatment, and the surface may have a coating layer.
[0046] <Resin layer> Examples of materials for the resin layer include urethane resin, polyethylene resin, polypropylene resin, ethylene vinyl acetate resin, etc. Among these, elastically deformable resin layers are particularly suitable for the hot melt adhesive of the present invention. The thickness of the resin layer is not particularly limited and can be appropriately selected depending on the desired impact absorption properties, the overall thickness of the resin laminate, and the like.
[0047] <Support layer> The main purpose of the support layer is to fix the resin layer, and therefore it is preferable that the support layer has a higher elastic modulus or rigidity than the resin layer. The support layer preferably has sufficient strength to withstand a load applied to the resin laminate and has impact absorption properties. Preferred examples of the material for the support layer include synthetic resin plate materials such as polyolefin resins such as polypropylene, and resins such as urethane resins, polystyrene, polyolefins, and rubber materials having a lower elastic modulus than the resin layer. The thickness of the support layer is not particularly limited and can be appropriately selected depending on the desired strength, impact absorption properties, the overall thickness of the resin laminate, and the like.
[0048] The resin laminate according to the present invention may have known layers or known structures other than those described above.
[0049] FIG. 1 shows an example of a preferred embodiment of the resin laminate according to the present disclosure, but it goes without saying that the present disclosure is not limited to this. FIG. 1 is a schematic cross-sectional view of an example of a resin laminate according to the present disclosure. The resin laminate 10 in Figure 1 has a surface layer 16, a resin layer 14, and a support layer 12, in that order, and has a layer (adhesive layer) 18a made of the hot melt adhesive of the present invention between the resin layer 14 and the surface layer 16, and further has a layer (adhesive layer) 18b made of the hot melt adhesive of the present invention between the support layer 12 and the resin layer 14.
[0050] (Method of manufacturing resin laminate) The method for producing the resin laminate of the present invention is not particularly limited, but a method for producing a resin laminate having a resin layer and a surface layer in this order is preferably a method including the steps of heating the hot melt adhesive of the present invention, applying the heated hot melt adhesive to the surface layer side of a member for forming a resin layer, and contacting the applied hot melt adhesive with a member for forming a surface layer to bond them together. In addition, a method for manufacturing a resin laminate having a support layer, a resin layer, and a surface layer in this order is preferably a method including the steps of heating the hot melt adhesive of the present invention, applying the heated hot melt adhesive to the support layer and bringing the applied hot melt adhesive into contact with a member for forming a resin layer to bond them together, and applying the heated hot melt adhesive to the side of the member for forming a resin layer that is not on the support layer side and bringing the applied hot melt adhesive into contact with a member for forming a surface layer to bond them together.
[0051] <Heating process> The method for producing a resin laminate according to the present invention preferably includes a step of heating the hot melt adhesive according to the present invention (also referred to as a "heating step"). The heating temperature in the heating step may be any temperature at which the hot melt adhesive of the present invention has sufficient fluidity, but is preferably 100°C to 240°C, more preferably 160°C to 240°C, and particularly preferably 170°C to 220°C. The heating means used in the heating step is not particularly limited, and known means such as a heater or a hot melt coater can be used.
[0052] <Adhesion processes A and B> A preferred embodiment of the method for producing a resin laminate consisting of a surface layer, a resin layer, and a support layer is a method including a step of applying the heated hot melt adhesive to the support layer, and bringing the applied hot melt adhesive into contact with a member for forming a resin layer to bond them together (also referred to as "adhesion step A"); and a step of applying the heated hot melt adhesive to the surface of the member for forming a resin layer other than the support layer, and bringing the applied hot melt adhesive into contact with a member for forming a surface layer to bond them together (also referred to as "adhesion step B"). In the adhesion step A, the heated hot melt adhesive according to the present invention is applied to a support layer, and a member for forming a resin layer is attached to the support layer to form an adhesive layer. In the bonding step B, the heated hot melt adhesive according to the present invention is applied to a resin layer-forming member, and a surface layer-forming member is bonded to the resin layer-forming member to form an adhesive layer. The order in which the bonding steps A and B are carried out is not particularly limited, and either step may be carried out first. The amount of hot melt adhesive applied in the bonding steps A and B may be selected independently and appropriately according to the desired thickness of the adhesive layer. The preferred thickness of each adhesive layer formed in the bonding steps A and B is the same as the preferred thickness of the adhesive layer described above. The coating means used in the bonding steps A and B is not particularly limited, and any known coating means such as a hot melt coater can be used. Among these, the coating in the bonding steps A and B is preferably performed by spray coating from the viewpoints of productivity and ease of coating.
[0053] The method for producing the resin laminate may include steps other than those described above. For example, from the viewpoint of waterproofness, airtightness, and the like, a step of applying a caulking agent to the outer periphery of the resin laminate may be included. The caulking agent is not particularly limited, and a known caulking agent or a hot melt adhesive may be used. EXAMPLES
[0054] The present invention will be specifically described below based on examples. Note that the present invention is not limited to these examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0055] (Examples 1 to 4 and Comparative Examples 1 to 3) <Preparation of hot melt adhesive> The components listed in Table 1 were mixed in the amounts listed in Table 1 under heating for approximately 30 minutes using an MS open-type kneader (manufactured by Moriyama Corporation) set at 230°C to produce the hot melt adhesives of Examples 1 to 4 and Comparative Examples 1 to 3, respectively.
[0056] <Preparation of resin laminate> Using the obtained hot melt adhesive, a resin laminate was produced as follows. The resin laminate used polypropylene (PP) (elastic modulus 32 MPa) as the support layer, elastically deformable polypropylene (PP) foam (elastic modulus 0.7 MPa) as the resin layer, and a flexible polypropylene (PP) sheet as the surface layer. The elastic modulus was measured at 25°C according to JIS K7161-1:2014 as follows. First, the test specimen was cut into a 10 mm wide specimen with a predetermined thickness (resin layer PP foam 4 mm, support layer PP 10 mm). The elastic modulus was calculated when the specimen was pulled at a pulling speed of 100 mm / min using a tensile tester. The hot melt adhesive was applied as follows. The tank temperature of the hot melt applicator (Suntool Corporation's Melter VH Series) was adjusted to 190°C, and the hot melt adhesive was sprayed from the curtain spray nozzle (Suntool Corporation) at a rate of 120 g / m. 2 After applying the adhesive to the support layer at a ratio of 120 g / m2, a resin layer is placed over it, and then the hot melt adhesive is sprayed on top of the resin layer at a rate of 120 g / m2. 2 After coating in a ratio of 0.5 kgf / cm, the surface layer was placed over the coating and pressed with a flat press. 2 The time was set to 9 seconds.
[0057] <Measurement of shear adhesive strength> The obtained hot melt adhesive was used to carry out the following evaluations. The hot melt adhesive was sandwiched between two Teflon (registered trademark) sheets and formed into a film-like hot melt adhesive with a thickness of 120 μm using a heating press adjusted to 140°C. This film-like hot melt adhesive was then transferred to an area of 25 mm x 25 mm on polypropylene plate A. Then, another polypropylene plate B is placed on top of it, and the pressure is 2 kgf / cm 2 The test pieces were then left to stand at 25°C for 16 hours, and then, in accordance with JIS K6850, the polypropylene plate A and the polypropylene plate B were pulled in opposite directions in the plane direction of the two polypropylene plates at a speed of 50 mm / min at 25°C, and the magnitude of the force at which shear failure occurred (shear adhesive strength) was recorded as the adhesive strength (MPa). The measurement results are shown in Table 1.
[0058] <Measurement of heat destruction temperature> A test piece obtained in the same manner as in the measurement of the shear adhesive strength was used, and a 200 g weight was attached to one end of the test piece, and the part with the weight attached was fixed so that the part with the weight was at the bottom in the weight direction. After leaving it at 38°C for 15 minutes, the temperature was raised at a rate of 0.4°C / min., and the temperature was measured when the adhesive part of the test piece could no longer withstand the load of the weight and the weight fell. The measurement results are shown in Table 1.
[0059] <Cold-heat cycle durability test> The resin laminate was left in a thermostatic chamber at 60° C. for 2 hours, and then in a thermostatic chamber at −20° C. for 2 hours. This cooling-heating cycle was repeated twice, and the resin laminate was left to cool to room temperature. The appearance of the resin laminate at this stage was observed.
[0060] <Workability evaluation (measurement of adhesion time)> A 120μm thick film of hot melt adhesive is applied to a 25mm x 25mm area on polypropylene plate A, and after leaving it in a 25℃ environment for a specified time, another polypropylene plate B is placed on top of it, and the adhesive is subjected to a pressure of 2kgf / cm2 The test piece obtained by pressing for 10 seconds at a pressure of 100 mm was left to stand at 25°C for 16 hours, and then the polypropylene plate A and the polypropylene plate B were pulled in opposite directions in the surface direction of the two polypropylene plates at a speed of 50 mm / min at 25°C in accordance with JIS K6850. The time at which the adhesive strength was 0.15 MPa or more was defined as the adhesive time. The time from when the adhesive was applied to an area of 25 mm x 25 mm on polypropylene plate A until another polypropylene plate B was placed on top of it was evaluated every 10 minutes up to a maximum of 30 minutes. A: The adhesive strength is 0.15 MPa or more after 10 minutes from overlapping. F: Adhesive strength after 10 minutes from overlapping is less than 0.15 MPa
[0061] [Table 1]
[0062] In Table 1, "*" indicates that the hot melt adhesive on the polypropylene plate A solidified and could not be bonded to the polypropylene plate B, and therefore each measurement value could not be measured. The abbreviations in Table 1 are explained in detail below. -Elastomer- SIS (1): Radial styrene-isoprene-styrene block copolymer (SIS), Quintac 3450, Zeon Corporation, MFR = 15 g / 10 min (200 °C, 5 kg) SIS (2): Linear styrene-isoprene-styrene block copolymer (SIS), Quintac 3520, Zeon Corporation, MFR = 7 g / 10 min (200 °C, 5 kg) SIS (3): Linear styrene-isoprene-styrene block copolymer (SIS), Kraton D1161J, Kraton, MFR = 12 g / 10 min (200 °C, 5 kg) SEBS: Linear styrene-ethylene / butylene-styrene block copolymer (SEBS) Kraton G1657, Kraton Corporation, MFR = 8g / 10min (200℃, 5kg) EVA: Ethylene-vinyl acetate copolymer, EV220ETR, manufactured by Mitsui Typhon Chemical Co., Ltd., MFR = 150g / 10min (190℃, 2.16kg)
[0063] -Tacky Fire- TF(1): C5 petroleum resin, T-REZ RB100, manufactured by JXTG Energy Corporation, softening point 100℃ TF(2): Rosin ester, Super Ester T-125, manufactured by Arakawa Chemical Industries, Ltd., softening point 125°C TF(3): Terpene phenol resin, YS Polystar S145, manufactured by Yasuhara Chemical Co., Ltd., softening point 145°C -Mineral oil- Mineral oil: SUNPURE N90-A, manufactured by Nippon Sun Oil Co., Ltd., aromatic hydrocarbon compound Ca / naphthene (cyclocyclic) hydrocarbon compound Cn / paraffin (aliphatic) hydrocarbon compound Cp = 5 / 43 / 52 (mass ratio), kinetic viscosity 92 mm 2 / s -Antioxidants- Antioxidant: hindered phenolic antioxidant, Sonnox 1010, manufactured by Songwon Industrial Co., Ltd.
[0064] As is clear from the results in Table 1, the hot melt adhesives of Examples 1 to 4, which are hot melt adhesives according to the present disclosure, and the resin laminates of Examples 1 to 4, which are resin laminates according to the present disclosure, have superior adhesive strength and superior thermal cycle durability compared to Comparative Examples 1 to 3. Furthermore, by using the hot melt adhesive according to the present disclosure, operations such as applying the adhesive and bonding between layers can be performed more easily than with conventional manufacturing methods, providing excellent workability and excellent productivity for resin laminates, etc. [Explanation of symbols]
[0065] 10: resin laminate, 12: support layer, 14: resin layer, 16: surface layer, 18a, 18b: layers (adhesive layers) made of the hot melt adhesive according to the present invention, PA: polyester plate A, PB: polyester plate B, W: weight
Claims
1. A film-like hot melt adhesive having a thickness of 120 μm is provided on a polypropylene plate A in an area of 25 mm × 25 mm, and then another polypropylene plate B is placed on top of the plate and pressed under a pressure of 2 kgf / cm2 for 10 seconds to obtain a test piece. The test piece is then allowed to stand at 25° C. for 16 hours, and then, in accordance with JIS K6850, the polypropylene plate A and the polypropylene plate B are pulled in opposite directions in the surface direction of the two polypropylene plates at a speed of 50 mm / min at 25° C., the adhesive strength being 0.15 MPa or more; A 200 g weight is attached to one end of the test piece, and the test piece is left to stand at 38° C. for 15 minutes. The temperature is then increased at a rate of 0.4° C. / min. When the bonded portion can no longer withstand the load of the weight and the weight falls, the temperature is 70° C. or higher. Contains an elastomer, a mineral oil, a tackifier, and an antioxidant; the elastomer comprises a styrene block copolymer; The content of the elastomer is 30% by mass or more and 50% by mass or less based on the total mass of the hot melt adhesive, The content of the mineral oil is 10% by mass or more and 20% by mass or less based on the total mass of the hot melt adhesive, The content of the tackifier is 30% by mass or more and 55% by mass or less based on the total mass of the hot melt adhesive, A hot melt adhesive, wherein the content of the antioxidant is 0.05 mass% or more and 1 mass% or less, based on the total mass of the hot melt adhesive.
2. The hot melt adhesive described in claim 1, wherein the mineral oil contains a paraffinic hydrocarbon compound.
3. The hot melt adhesive according to claim 1 or 2, wherein the styrene block copolymer comprises a styrene-isoprene-styrene block copolymer.
4. The hot melt adhesive according to any one of claims 1 to 3, which is a hot melt adhesive for producing a resin laminate comprising an elastically deformable resin layer and a flexible surface layer.
5. A hot melt adhesive described in any one of claims 1 to 4, wherein the styrene block copolymer comprises a radial styrene-isoprene-styrene block copolymer and a linear styrene-isoprene-styrene block copolymer.
Citation Information
Patent Citations
Hot-melt adhesive composition
JP1989144483A
Precoated surface material for vehicular interior material and manufacturing method of vehicular interior material
JP2004284575A
Wiring sheet
JP2020064889A